Income Inequality and It’s Contribution to Market Failure and Solutions from an Islamic Perspective - Cherno Jallow; Hamidou Jallow (Journal of Islamic Finance, 2024)
This study explores the intricate dynamics of income inequality and its impact on market failure, with a particular focus on the Islamic perspective and the Gambian context. The persistence of income inequality poses significant challenges, particularly in developing nations, affecting consumption, production, savings, and investment levels, thereby impeding optimal resource allocation and productive efficiency. This market failure is further exacerbated by the concentration of resources among a small economic segment. Islam offers robust mechanisms, such as zakat and waqf, to address poverty and enhance income equality, promoting a more equitable and progressive society. The research encompasses a comprehensive literature review, examining various studies on income inequality, poverty, and market failure from both conventional and Islamic perspectives. It also highlights the detrimental effects of income inequality on economic growth. Furthermore, the study explores the fiscal policies and their impact on poverty and income inequality in The Gambia, revealing a complex relationship between these factors. Furthermore, the research investigates absolute poverty and its contribution to market failure. The study utilizes various measures, such as the Gini Coefficient, to assess income inequality and explores the economic and social implications of this disparity. By integrating both conventional and Islamic approaches, the study offers a multifaceted understanding of the mechanisms to curb income inequality and promote economic growth and social equity.